Snails and slugs - Nurul Syafiqah, Nasir; Mohd Zacaery, Khalik (UNIMAS Publisher, Sarawak Energy Berhad and Natural History Publications (Borneo) Sdn. Bhd., 2024)
The class Gastropoda comprises snails, semi-slugs and slugs. A snail has an organic to calcareous coiled shell, into which its soft body can be fully retracted. On the other hand, a semi-slug shows a reduced shell that is embedded under the mantle tissue, which does not accommodate the soft tissue. Lastly, a slug lacks a shell on top of its soft body. Generally, the terms ‘snails and slugs’ are used to refer to gastropods. They occupy a wide range of habitat types (e.g., terrestrial, freshwater, and marine), showcasing their ability to thrive in a variety of environments.